The vertical light-gradient and its potential impact on animal distribution and behavior - Nilsson, Dan-E; Smolka, Jochen; Bok, Michael (Frontiers in Ecology and Evolution, 2022)
The visual environment provides vital cues allowing animals to assess habitat quality, weather conditions or measure time of day. Together with other sensory cues and physiological conditions, the visual environment sets behavioural states that make the animal more prone to engage in some behaviours, and less in others. This master-control of behaviour serves a fundamental and essential role in determining the distribution and behaviour of all animals. Although it is obvious that visual information contains vital input for setting behavioural states, the precise nature of these visual cues remains unknown. Here we use a recently described method to quantify the distribution of light reaching animals’ eyes in different environments. The method records the vertical gradient (as a function of elevation angle) of intensity, spatial structure and spectral balance. Comparison of measurements from different types of environments, weather conditions, times of day, and seasons reveal that these aspects can be readily discriminated from one another. The vertical gradients of radiance, spatial structure (contrast) and colour are thus reliable indicators that are likely to have a strong impact on animal behaviour and spatial distribution.